OS05.3.A Temporal muscle thickness as surrogate parameter of sarcopenia in newly diagnosed glioblastoma patients:translational imaging analysis of the CENTRIC EORTC 26071-22072 and CORE trials. (9th September 2021) - Furtner, J; Weller, M; Weber, M; Gorlia, T; Nabors, B; Reardon, D; Tonn, J; Stupp, R; Preusser, M
Abstract: BACKGROUND: Temporal muscle thickness (TMT) was described as surrogate parameter of skeletal muscle mass. This study aimed to investigate the prognostic relevance of TMT in patients with newly diagnosed glioblastoma. MATERIAL AND METHODS: TMT was assessed in cranial magnetic resonance images (MRI) of 755 pts enrolled in the CENTRIC EORTC 26071-22072 study (n=508) and CORE study (n=247). Predefined sex-specific TMT cutoff values were used to categorize "patients at risk of sarcopenia" and "patients with normal muscle status" at baseline. Furthermore, patients were categorized according to the extent of TMT loss over time. Cox models adjusted for other explanatory variables were used to evaluate the associations with progression-free survival (PFS) and overall survival (OS). RESULTS: Overall, 510/755 (67.6%) patients were categorized as "at risk of sarcopenia" and 245/755 (32.4%) patients had normal muscle status at baseline. In both study cohorts patient at risk of sarcopenia at baseline had significantly higher risk of progression and death than patients with normal muscle status (CENTRIC: PFS = HR 0.16, 95% CI: 0.12, 0.21, p<0.001; OS = HR 0.341, 95% CI: 0.27, 0.44, p < 0.001; CORE: PFS = HR 0.29, 95% CI: 0.21, 0.39, p<0.001; OS = HR 0.365, 95% CI: 0.27, 0.49, p<0.001). In multivariate Cox models adjusted for other important prognostic parameters similar results were obtained. In patients at risk for sarcopenia the extent of TMT loss over time showed a significant inverse correlation with median OS times (CENTRIC: p < 0.001, CORE: p = 0.005, log-rank test), but not in patients with normal baseline muscle mass in both study cohorts (CENTRIC: p = 0.538, CORE: p = 0.28, log-rank test). CONCLUSION: TMT identifies patients with newly diagnosed glioblastoma at risk for progressive sarcopenia and adverse outcomes. Early intervention for muscle mass preservation including exercise and resistance training as well as nutritional support may prevent skeletal muscle loss and improve patient outcome in this group of patients.